2018
DOI: 10.1111/jerd.12427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light absence or attenuation on biaxial flexural strength of dual‐polymerized resin cements after short‐ and long‐term storage

Abstract: Objective To evaluate whether biaxial flexural strength (BFS) of dual resin cements is affected by light absence or attenuation, storage time, or cements' chemical nature. Materials and methods One hundred and twenty disk‐shaped specimens were made from each cement (non‐self‐adhesive cement and self‐adhesive cement) using Teflon molds on a controlled temperature surface (35°C). Specimens were polymerized as follows (N = 30): self‐cured, directly light‐cured, light‐cured at a distance of 6 mm between the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…According to the polymerization reaction mechanism, resin cements can be classified into self-cure, light-cure and dual-cure categories (Table 2) [5,45,63].…”
Section: Polymerization Mechanism Of Resin-based Dental Luting Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the polymerization reaction mechanism, resin cements can be classified into self-cure, light-cure and dual-cure categories (Table 2) [5,45,63].…”
Section: Polymerization Mechanism Of Resin-based Dental Luting Materialsmentioning
confidence: 99%
“…An ample body of evidence also shows that the light beam weakens as it passes through the restoration material, making it difficult to achieve the intensity required for the polymerization of resin cement in deep and inaccessible parts of the tooth preparation. Consequently, a less successful and efficient polymerization of the resin cement is expected, which may lead to increased hydrolytic degradation, microleakage and the presence of secondary caries [5]. The aforementioned challenges can be mitigated by combining chemical and light-induced polymerization [13], which requires a dual polymerizing catalyst [65,66].…”
Section: Polymerization Mechanism Of Resin-based Dental Luting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inadequate polymerization of camphorinon causes the discoloration to yellow shades. Some resin cements were produced photo-initiator tertiary amine free to prevent discoloration [ 12 , 13 ]. It has been reported that new resin cements without tertiary amine show much less discoloration.…”
Section: Introductionmentioning
confidence: 99%
“…12 Dual-cured resin cements that are prepared by both chemically activated and photoactivated mechanisms are frequently used for cementation of indirect restorations 13,14 because light attenuation occurs beneath the restorative materials, especially in deep areas of the preparation. 15 For the sake of improving the handling properties and reducing the procedure time, self-adhesive resin cements that eliminate pretreatment of the tooth structure have been widely used. 16 Some dualcured self-adhesive resin cements demand surface treatment, including both sandblasting and silanization on CAD/CAM resin blocks.…”
mentioning
confidence: 99%